On issue of Nikifor Chernigovsky’s citizenship in connection with development of Amur region by Russia - M. S. Novikov (Омский научный вестник: Серия "Общество. История. Современность", 2021)
Interpretations of the events of the distant past of the Russian state have now become the arena of not only ideological, but also geopolitical struggle for territories and resources. One of the most pressing issues is the ownership of Siberia and its separate territories of Russia. The purpose of this article is to analyze the origin and citizenship of the participant in the development of the Amur region, Nikifor Chernigovsky, whose achievements, as a citizen of Poland and Ukraine, are claimed by some public figures of these states. The author concludes that, regardless of ethnic origin, Nikifor Chernigovsky participated in the Russian development of the Amur region neither as an initiative Polack or Ukrainian, nor as a foreigner in the Russian service, but as an Orthodox Christian and a citizen of the Russian state